Indonesia : Selected Issues. (IMF Staff Country Reports; Country Report, 2011)
This study estimated Indonesia's potential growth rate and examined its underlying determinants. Implementing a comprehensive program to address key influencing issues can improve the effectiveness of monetary policy, increase financial stability, and support capital market development. This paper also reviews the level and structure of tax revenues in Indonesia, estimates tax effort and tax efficiency, and discusses potential areas of revenue mobilization. Indonesia's financial linkages to the rest of the world have become stronger and more diversified, which increases its exposure to systemic risks.